AYAM SEBAGAI OBJEK DALAM KARYA BATIK DAN SULAM - Alfi Sania; Erwin Erwin (Universitas Negeri Padang, 2021)
The purpose of the creation of these final works to visualize forms of native chicken behavior into written batik and embroidery. This work embodies the unique forms of daily chicken behavior village. The menthod in the work’s realization though several stages is: preparation, elaboration, synthesis, realization of concepts and completion. The embodied work was called: striving, foraging, blending love, duel 1, duel2, duel 3, love children, crowing, warmth, protection.Keywords: Chicken, Batik Wrote, Embroidery